SIMULATION MODELING AND IMPROVEMENT OF THE WINDING DRUM COOLING CONDITIONS - Buzauova, Toty; Amanov, Erlan; Kaizait, Zhuldyzay; Mudrakov, Vladimir; Sivachenko, Leonid (Journal of Applied Engineering Science, 2024)
At the Kaz-Metiz LLP plant, there has long been a problem of insufficient drums cooling due to the scale formation, which led to the need for frequent production stops to cool them. To solve this problem, simulation modeling of cooling drums with and without scale was carried out to investigate the heat spread over the body. The results of the stationary analysis in the Ansys application showed the heat propagation across the cross-section of the drum and proved that the resulting scale, having a low thermal conductivity, significantly reduces the heat exchange from the drum wall to water, as a result, the surface of the drum is significantly overheated. Subsequently, the improved drum cooling system was implemented in «Kaz-Metiz» LLP.
Keywords: winding drums, temperature, simulation modeling, Ansys application program, thermal conductivity, cooling, thermal analysis